EFEKTIVITAS USIA 17 TAHUN PADA SIM C GUNA MENGURANGI KECELAKAAN LALU LINTAS SURAKARTA - Wibowo, Uce Ade; Widada, Sutapa Mulja (PARENTAL, 2013)
The objecetive of research was to describe for find out about efectiveness of Article 81 Verse (2) Letter a of Act Number 22 of 2009 concern age requisite to get SIM C. Then, which factors can influence efectiveness of Article 81 Verse (2) Letter a of Act Number 22 of 2009. And, which effort can do for decrease traffic accident at teenager. This study belonged to an emperical law reserch that was descriptive in nature. Primary data was from observation and interview result. Secondary data was from library study on law, archive, and other document relevant to the research studied. Techniques of collecting data used were document, observation, and interview. Based on result of research that Article 81 condition 17th old, to age 20th old, then establish which independent institute for handle safety riding and traffic accident problem at teenager. Verse (2) Letter a of Act Number 22 of 2009, not effective for decrease traffic accident in Surakarta. Factor causing are legislation; upholder of the law; Facilitiy of uphold law; society; and culture. Effort for decrease traffic accident are increase from age